Modified Arrhenius kinetics for double base propellant decomposition: effect of water - Romero Jabalquinto, Alonso; Mai, Nathalie; Belghiche, Samira; Gill, Philip P. (Elsevier, 2024)
Numerous studies have been conducted on the decomposition mechanisms of cellulose nitrate (NC), a polymer employed in double base (DB) rocket propellants. It is well known that storage temperature affects the lifetime of these energetic formulations. However, less studies have been published on the influence of water. This research examined the role of water on the stabiliser consumption rate during accelerated ageing of a DB rocket propellant, as well as the impact on the shelf life prediction of the energetic formulation. Different volumes of water (0.8, 1.6, 2 and 4 µl/g) were added to the propellant in sealed vials, which were then isothermally aged (70, 80, 90, 100 °C). Analyses of the stabiliser consumption showed a faster decomposition kinetics in presence of water which is indirectly linked to the shortening of the storage life of the NC based propellant by 35 %. For the conditions, an activation energy of 133 ± 4 kJ/mol was reported for the water catalytic decomposition mechanism. A numerical model that included water as a variable was reported to reduce the uncertainty in the determination of the service life of NC based propellant. International standards such as Allied Ordnance Publication 48 should not overlook the effect of water/moisture on the safety of ammunition containing NC and should implement a modified Arrhenius equation.
Keywords: Double base rocket propellant; Life assessment; Stabilizer depletion; Water effect; Modified Arrhenius kinetics